Low Power Techniques for a Mixed-Signal Circuit - Khalek, Faizal; Yusoff, Zubaida; Sulaiman, Mohd-Shahiman (2007)
This paper presents analyses performed on design techniques implemented on a mixed-signal circuit with the goal of minimizing static and dynamic power consumptions. The concept of multi-Vdd and multi-Vth is implemented through design parameter manipulation hence not having to change or require expensive process. The techniques are applied on a digital circuit, a Phase Detector, as well as on an analog circuit, a voltage-controlled oscillator. The results suggest a potential reduction of 30% in total power consumption for a digital circuit and 55% for a power-hungry VCO circuit.